Treatment of Superficial Vein Thrombosis: A Systematic Review and Meta-Analysis - Duffett, Lisa; Kearon, Clive; Rodger, Marc; Carrier, Marc (Thrombosis and Haemostasis, 2019)
Background The optimal first line treatment for patients with isolated superficial venous thrombosis (SVT) of the lower extremity is unknown.Objective This article reports estimates of the rate of venous thromboembolic complications among patients with SVT according to treatment.Materials and Methods A systematic review and meta-analysis was performed using unrestricted searches of electronic databases. Reported events were transformed to event per 100 patient-years of follow-up and a random effects model was used to calculate pooled rates according to pre-specified treatment categories. The primary outcome was the occurrence of deep vein thrombosis (DVT) or pulmonary embolism (PE) during the study follow-up period.Results Seventeen articles, including 6,862 patients, were included in the meta-analysis. Fondaparinux had the lowest event rate with 1.4 events per 100 patient-years of follow-up (95% confidence interval [CI], 0.5–2.8, I2 = 18%). Pooled event rates for DVT or PE ranged from 9.3 to 16.6 events per 100 patient-years across other treatment categories, and the pooled event rate for no treatment/placebo was 10.5 events per 100 patient-years (95% CI, 3.0–22.0). Major bleeding was low and similar across all treatment categories. Heterogeneity was moderate to high for most pooled estimates.Conclusion While pooled event rates suggest that fondaparinux achieves the lowest rate of DVT or PE, low-quality evidence for other treatments prevents firm conclusions about the optimal treatment for SVT.
Keywords: superficial vein thrombosis; thrombophlebitis; systematic review; anticoagulants; anti-inflammatory agents